Two Co-occurring Liana Species Strongly Differ in Their Hydraulic Traits in a Water-Limited Neotropical Forest - Coppieters, Kasper; Verbeeck, Hans; Dequeker, Simon; Powers, Jennifer S.; Vargas G., German; Smith-Martin, Chris M.; Steppe, Kathy; Meunier, Félicien (Frontiers in Forests and Global Change, 2022)
Lianas are a key growth form in tropical forests. They are believed to be strong competitors for water, thanks to their presumed efficient vascular systems. However, despite being a large polyphyletic group, they are currently often considered as a functionally homogeneous entity. In this study, we challenged this assumption by estimating the variability in hydraulic traits of two common, co-occurring liana species in a water-limited environment, namely a seasonally dry tropical forest in Costa Rica. We measured vulnerability to embolism at the leaf and branch levels using two different methods (optical and acoustic vulnerability) and found that both species had very different hydraulic properties. Compared to reported P50 values in literature, we found two extreme P50 values: a low value for Bignonia diversifolia (-4.30 ± 0.54 MPa at the leaf level; -7.42 ± 0.54 MPa at the branch level) and a high value for Cissus microcarpa (-1.07 ± 0.14 at the leaf level; -1.20 ± 0.05 MPa at the branch level). Furthermore, B. diversifolia had a higher apparent modulus of elasticity in the radial direction (556.6 ± 401.0 MPa) and a variable midday water potential. On the other hand, C. microcarpa had a low apparent modulus of elasticity in the radial direction (37.8 ± 26.3 MPa) and a high branch water content, which enabled the species to keep its water potential stable during the dehydration experiments and during a drought period in the field. This mechanism may enable this species to coexist with species that are more resistant to drought-induced embolisms such as B. diversifolia. Although only two species were studied, considerable overlap was found between the range of hydraulic properties of trees growing in the same location and trees and lianas growing in two forests in Panama. These findings demonstrate that lianas cannot be considered as a homogeneous group and call for further research into the intra-growth form diversity of liana properties.